Ocean Economic Linkage in Economic Development of Island Province - Chairullah Amin; Heti Mulyati; Eva Anggraini; Tridoyo Kusumastanto (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The importance of the ocean economy in island regional development requires the local government to formulate relevant policies according to the potential of its ocean economic activities. Based on the 2012 North Maluku Province I-O table updated to 2016, this study was conducted by aggregating 20 ocean subsectors to measure inter-sectoral linkages, output multipliers, income multipliers, and labor multipliers in the ocean economic sector. The I-O analysis results show that the leading sectors of the ocean economy of North Maluku Province are fisheries, ore mining, and construction. The marine sector which has excellent development potential in the economic development of North Maluku Province is based on the output multiplier, namely the metal ore mining sector, the food, and beverage industry, marine transportation, and the provision of food and beverage. Based on the number of labor multipliers, the education service, construction, and ore mining sectors can absorb high labor compared to other sectors.